Effect of HHFNC therapy on organ oxygenation and brain metabolism in neonates receiving exchange transfusion - Li, Wanting; Ye, Ruming; Xie, Binyan; Deng, Xiaofang; Li, Dan; Lin, Ying; Wu, Guanhong; Huang, Xianghui (Frontiers in Pediatrics, 2024)
Background: Exchange transfusion therapy is a complex and invasive procedure with a high-risk coefficient. This method involves replacing the entire blood of a child with fresh blood with double circulating blood volume in a short period, typically in 1 ~ 2 hours. This procedure can cause the body’s internal environment to be unstable, which can put newborns under a lot of stress. This stress can lead to many, including abnormal laboratory biochemical examination, low or high blood pressure, and et al. This study investigated the effects of a Humidified high-flow nasal cannula(HHFNC) ventilation on hemodynamic stability and oxygenation during exchange transfusion in neonates. Furthermore, the effects on brain metabolism and salivary cortisol during exchange transfusion were also analyzed. Method: In this study, the control group consisted of 45 cases of children . The observation group consisted of 33 cases of children who underwent blood exchange under HHFNC support between January 1, 2020, and April 30, 2022. The study compared various physiological parameters between the control and the observation group. These included blood gas analysis, relevant clinical indicators, tissue oxygen saturation, hemodynamics. Furthermore, the study also compared the changes in brain metabolic and salivary cortisol indicators between the two groups of children. Results: The results did not reveal any significant difference in PH, PaO2, and duration of blood exchange between the control and the observation group. However, the observation group’s invasive mean arterial pressure, ejection fraction, cerebral oxygenation, intestinal oxygenation, and renal oxygenation were higher than those of the control group. Furthermore, compared with the control group, the pulmonary artery pressure, heart rate, and PaCO2 were lower in the observation group. The difference was statistically significant. The NAA/Cho and Cho/Cr values of the two groups of children were also significantly different. Conclusion: During blood exchange, unstable hemodynamics substantially impact organ oxygenation. The results of this study suggest that HHFNC and specific ventilation pressure support can improve the respiratory rate and help maintain blood flow stability and organ oxygenation. This technique may also reduce adverse reactions caused by blood exchange, minimizing patient stress and reducing the impact on brain metabolism.